Prevalensi Preeklamsi dengan Komplikasi di Rumah Sakit Rujukan Kabupaten Banyumas Tahun 2017-2020 - Wiwit Wulandari; Wilis Dwi Pangesti (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Preeclampsia eclampsia is the leading cause of perinatal morbidity and mortality with an estimated 50,000-60,000 deaths related to preeclampsia per year. Preeclampsia-eclampsia reaches 3-10%, and is the highest cause of maternal death in addition to bleeding and infection. This research is a quantitative research with a descriptive survey design. The sample consisted of 186 medical record data for pregnant women with preeclampsia at the Banyumas Regency referral hospital from 2017 to 2020. This research data was obtained from medical record data at 2 Bnyumas Regency Referral Hospitals in 2017-2020. Samples were taken from Banyumas Hospital and Ajibarang Hospital in 2017-2020. The sample criteria, pregnant women with preeclampsia accompanied by complications (eclampsia, pulmonary edema, HELLP syndrome) and complications in infants (IUGR and IUFD), the period of time for examination of pregnant women in 2017-2020. Data were analyzed using SPSS 22. The prevalence of preeclampsia with complications at the Banyumas Regency referral hospital in 2017-2020 was 2.30%. The characteristic of PDK is MAP > 90, which is 100% which is experienced by the majority of respondents. Complications of PDK consisted of PDK in the mother, namely 7.52% and PDK in infants, which was 10.75%. PDK in mothers who entered the ICU was 26.47%. The prevalence of preeclampsia with complications in mothers at the Banyumas Regency Referral Hospital in 2017-2020 was 34 cases (2.30%).